أثر برنامج تدريبي في الوسط المائي على تنمية قدرة الإسترجاع لدى لاعبي كرة اليد اقل من 17 سنة - Zakaria hamed mansour, azizi; Amenellah , rachid (sports creativity, 2025)
This research aims to use training program in the aquatic environment to develop the recovery capacity of handball players under 17years old, this program contains 8weeks, 3 trainings each week. The samples represent handball players of the sport club: Wifak TISSEMSSILT. Using the experimental method For it suitability to this study. The pre-test and post-test method were applied to control and experimental samples which represent 18members (chosen in deliberately way). We applied to the experimental group a Rufi test to measure the recovery capacity and training program in aquatic environment. We found statistically significant differences between the two groups for the benefit of the experimental one in the post-test, indicating the effectiveness of this training program to improve the recovery capacity, so we recommend the application of modules for recovery in the aquatic environment